One-year mortality after severe COPD exacerbation in Bulgaria - Evgeni Mekov; Yanina Slavova; Adelina Tsakova; Marianka P. Genova; Dimitar T. Kostadinov; Delcho Minchev; Dora Marinova; Mihail A. Boyanov (PeerJ, 2016)
Introduction One-year mortality in COPD patients is reported to be between 4% and 43%, depending on the group examined. Aim To examine the one-year mortality in COPD patients after severe exacerbation and the correlation between mortality and patients’ characteristics and comorbidities. Methods A total of 152 COPD patients hospitalized for severe exacerbation were assessed for vitamin D status, diabetes mellitus (DM), arterial hypertension (AH), and metabolic syndrome (MS). Data were gathered about smoking status and number of exacerbations in previous year. CAT and mMRC questionnaires were completed by all patients. Pre- and post-bronchodilatory spirometry was performed. One-year mortality was established from national death register. Results One-year mortality is 7.2%. DM, MS, and VD are not predictors for one-year mortality. However there is a trend for increased mortality in patients with AH (9.5% vs. 2.1%, p = 0.107). There is increased mortality in patients with mMRC > 2 (11.1 vs. 0%, p = 0.013). The presence of severe exacerbation in the previous year is a risk factor for mortality (12.5% vs. 1.4%, p = 0.009). There is a trend for increased mortality in the group with FEV1 < 50% (11.5 vs. 4.4%, p = 0.094). Cox regression shows 3.7% increase in mortality rate for 1% decrease in FEV1, 5.2% for 1% decrease in PEF, 7.8% for one year age increase and 8.1% for 1 CAT point increase (all p < 0.05). Conclusions This study finds relatively low one-year mortality in COPD patients after surviving severe exacerbation. Grade C and FEV1 > 80% may be factors for good prognosis. Risk factors for increased mortality are age, FEV1 value, severe exacerbation in previous year and reduced quality of life.